KESULITAN SISWA MEMBACA TEKS BAHASA ARAB DALAM PEMBELAJARAN MAHARAH QIRO'AH - Aini, Syarifah; Yunus, Machmud; Aminatusshalihah, Tiara (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2023)
Students have difficulty reading or understanding the contents of a text in Arabic lessons so that it has an impact on low Arabic learning outcomes. Though the ability to read has a very important role in learning Arabic also in everyday life. This study aims to obtain data about the difficulty factors of VII grade MTs students Ash-Shiddiqin Panaragan in reading Arabic text. This research used descriptive method with qualitative approach. In this study, which is the subject of research is the students of class VII MTs Ash-Shiddiqin Panaragan academic year 2022/2023. The results of the study revealed that the difficulty factors of Class VII students in reading Arabic texts could be classified into two factors. First, internal factors include the ownership experience and language competence of students was low, less interest in reading students, and students motivation is low. Second, external factors, include factors of teachers who lack the mastery of the material, learning methods that are less attractive, the attitude of the teacher in the learning process assessed to be less enthusiastic, lack of instructional media used, the mobility of the position of a teacher in a classroom that is lacking in monitoring student activities, and lack of availability of textbooks.